Quattro villas en Ypenburg : La Haya, Holanda 2000 - MVRDV (2002)
Proyecto de cuatro viviendas a doce metros sobre el nivel del mar
Keywords: MAAS, WINY; RIJS, JACOB VAN; VRIES, NATHALIE DE; VIVIENDAS APAREADAS; PAISES BAJOS; LA HAYA